1989
DOI: 10.1111/j.1744-7348.1989.tb06577.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate accumulation in vegetables and its relationship to quality

Abstract: SummaryMany plants, especially leafy vegetables, accumulate nitrate under low light conditions as uptake of nitrate exceeds reduction. Nitrate may harm the health of the consumer as it can be converted to nitrite causing methaemoglobinaemia or carcinogenic nitrosamines. To take directional measures during the growth of vegetables which will decrease the nitrate content, physiological knowledge about the nitrogen economy of the plant is needed. In this review the physiological role of nitrate as osmoticum and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
2
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(79 citation statements)
references
References 40 publications
5
67
2
5
Order By: Relevance
“…NO 3 and carbohydrates are involved in osmotic adjustment; specifically, their relationship is inversely proportional and is regulated by the intensity of light [36][37][38]. In this study, P-shortages seemed to reduce the N intake and increase carbohydrate production in the lettuce cultivated in system A.…”
Section: Discussionmentioning
confidence: 87%
“…NO 3 and carbohydrates are involved in osmotic adjustment; specifically, their relationship is inversely proportional and is regulated by the intensity of light [36][37][38]. In this study, P-shortages seemed to reduce the N intake and increase carbohydrate production in the lettuce cultivated in system A.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, nitrate, amino acids, proteins, sugars, organic acids, mineral, and vitamins are closely interrelated (Blom-Zandstra 1989;Huang et al 2011). Our previous study suggested that the overall quality of cucumbers was improved by applying VP and VPinorganic mixed fertilizer under greenhouse conditions (Zhao et al 2010a, b).…”
Section: Yield and Quality Responses To Soil Vermicompost Amendmentmentioning
confidence: 99%
“…Under conditions of increased nitrogen supply the potato crop has the ability to take up nitrogen in excess to that required for growth and store it as nitrate in the vacuoles (Millard and Marshall 1986). Potato tubers normally have low nitrate content, not exceeding 300 mg kg -1 in fresh matter (Blom-Zandstra 1989). The nitrate content of the tubers depends on cultivar, availability of nitrogen during tuber growth and environmental factors.…”
Section: Introductionmentioning
confidence: 99%